Cardiotonic Activity of Aqueous Extract of Emblica officinalis Fruits - MASTAN, S.K.; ESWAR KUMAR, K.; BABU, S.M.; DAS, M.CH.; CHAITANYA, G. (Asian Journal of Chemistry, 2010)
Emblica officinalis is known for its medicinal and therapeutic properties from the ancient time in India and considered as a wonder fruit for health conscious population. It is one of the important herbal drugs used in Unani (Graeco-Arab) and Ayurvedic systems of medicine. It is used both as a medicine and as a tonic to build up lost vitality and vigour. In Unani medicine, it is described as a cardiotonic. Although acclaimed traditionally as cardiotonic there are not many scientific studies regarding the cardiotonic activity of Emblica officinalis. The present study was conducted to evaluate the cardiotonic activity of aqueous extract of Emblica officinalis (EAE) fruits in graded doses using frogheart in situ preparation (normal and hypodynamic condition) and to explore the possible mechanism of action by conducting interaction study of EAE with β-blocker (propranolol) and calcium-channel blocker (Diltiazem). Enzyme studies such as Na+K+ATPase, Ca2+ ATPase and Mg2+ ATPase were done on the heart tissue aspartate transaminases (AST), alanine transaminases (ALT), lactate dehydrogenase (LDH) and creatine phosphokinase (CPK) were estimated in the heart tissue and serum of albino rats after administering the extract for 7 d. The aqueous extract of Emblica officinalis fruits exhibited a cardiotonic activity and its possible mechanism of action is through calcium channels.